TRIGONOMETRY AND MODEL SIMPLE HARMONIC MOTION - Mamadjanova, Mamurakhon Kadirjanovna; Majidov , Orifjon Obidjon o‘g‘li; Ibaydullayev , Tolanboy Tursunboyevich (Educational Research in Universal Sciences, 2023)
A mere snippet of a song from the past can trigger vivid memories, including emotions ranging from unabashed joy to deep sorrow. Trigonometric functions describe the pitch, loudness, and quality of a music notes. In this article we will learn how trigonometry models harmonic motion.